2007
DOI: 10.2746/042516407x217876
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of serum antibody response toAnoplocephala perfoliatain relation to parasite burden and faecal egg count

Abstract: In the population of Danish horses investigated the serum ELISA test should be interpreted such that horses in need of anti-Anoplocephala treatment have an OD = 0.7 or above.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 23 publications
3
43
0
2
Order By: Relevance
“…The infection intensity and the stage of parasite maturity decide on the sensitivity of the sedimentation–flotation methods. Kjaer et al (2007) provided evidence that the detection of A. perfoliata invasion increases to 89 % when the intensity of infection is higher than 20 tapeworms with uterine segments.…”
Section: Discussionmentioning
confidence: 99%
“…The infection intensity and the stage of parasite maturity decide on the sensitivity of the sedimentation–flotation methods. Kjaer et al (2007) provided evidence that the detection of A. perfoliata invasion increases to 89 % when the intensity of infection is higher than 20 tapeworms with uterine segments.…”
Section: Discussionmentioning
confidence: 99%
“…Faecal egg counts have previously been shown in other odd-toed ungulates and with similar parasite groups to be a broadly reliable indicator of parasite abundance (Nielsen et al 2010;Stringer et al 2014). For instance, Kjaer et al (2007) found a positive correlation of 0.71 between worm burden and faecal egg count for the tapeworm Anoplocephala perfoliata in domestic horses (Equus ferus caballus). Interestingly, the high abundance of eggs within faecal samples found in black rhino may increase the accuracy of faecal egg counts (Denwood et al 2012).…”
Section: Methodsmentioning
confidence: 98%
“…Another important difference between these species is that only A. perfoliata has been reported to cause pathological reactions around their attachment site (Fig 1), characterised by hyperaemia, mucosal thickening and necrotic ulcers (Pearson et al 1993;Nilsson et al 1995;Williamson et al 1997;Kjaer et al 2007). Another important difference between these species is that only A. perfoliata has been reported to cause pathological reactions around their attachment site (Fig 1), characterised by hyperaemia, mucosal thickening and necrotic ulcers (Pearson et al 1993;Nilsson et al 1995;Williamson et al 1997;Kjaer et al 2007).…”
Section: Introductionmentioning
confidence: 99%